Recomendação multi-contextual de eventos em redes sociais de eventos. - MACEDO, Augusto Queiroz de. (2015)
Submitted by Johnny Rodrigues (johnnyrodrigues@ufcg.edu.br) on 2018-05-08T15:41:02Z No. of bitstreams: 1 AUGUSTO QUEIROZ DE MACEDO - PPGCC 2015..pdf: 6968007 bytes, checksum: 87fa2564456dfd56be7e711e21a082df (MD5)